Metabolic engineering of Ashbya gossypii for deciphering the de novo biosynthesis of γ-lactones - Silva, Rui (2019)
Background Lactones are highly valuable cyclic esters of hydroxy fatty acids that find application as pure fragrances or as building blocks of speciality chemicals. While chemical synthesis often leads to undesired racemic mixtures, microbial production allows obtaining optically pure lactones. The production of a specific lactone by biotransformation depends on the supply of the corresponding hydroxy fatty acid, which has economic and industrial value similar to γ-lactones. Hence, the identification and exploration of microorganisms with the rare natural ability for de novo biosynthesis of lactones will contribute to the long-term sustainability of microbial production. In this study, the innate ability of Ashbya gossypii for de novo production of γ-lactones from glucose was evaluated and improved. Results Characterization of the volatile organic compounds produced by nine strains of this industrial filamentous fungus in glucose-based medium revealed the noteworthy presence of seven chemically different γ-lactones. To decipher and understand the de novo biosynthesis of γ-lactones from glucose, we developed metabolic engineering strategies focused on the fatty acid biosynthesis and the β-oxidation pathways. Overexpression of AgDES589, encoding a desaturase for the conversion of oleic acid (C18:1) into linoleic acid (C18:2), and deletion of AgELO624, which encodes an elongase that catalyses the formation of C20:0 and C22:0 fatty acids, greatly increased the production of γ-lactones (up to 6.4-fold; (7.6 ± 0.8) × 103 µg/gCell Dry Weight). Further substitution of AgPOX1, encoding the exclusive acyl-CoA oxidase in A. gossypii, by a codon-optimized POX2 gene from Yarrowia lipolytica, which encodes a specific long chain acyl-CoA oxidase, fine-tuned the biosynthesis of γ-decalactone to a relative production of more than 99%. Conclusions This study demonstrates the potential of A. gossypii as a model and future platform for de novo biosynthesis of γ-lactones. By means of metabolic engineering, key enzymatic steps involved in their production were elucidated. Moreover, the combinatorial metabolic engineering strategies developed resulted in improved de novo biosynthesis of γ-decalactone. In sum, these proof-of-concept data revealed yet unknown metabolic and genetic determinants important for the future exploration of the de novo production of γ-lactones as an alternative to biotransformation processes.